DEVELOPMENT AND COMMODITY EVALUATION OF SEMI-SMOKED SAUSAGES USING PASTE-LIKE CONCENTRATES FROM AMARANTH AND LUPINE SEEDS - Xurshida Asqarova Ekram qizi, Eshmuratov Marat Tangatarovich (American Journals, 2022)
The article gives a descriptive characteristic of lupine and amaranth seeds (historical development, chemical composition, use in the food industry). The principle of operation of a mechanoacoustic homogenizer is considered. Based on the analysis of the principles of quality management, qualimetric tools for assessing the quality of pasty concentrates and products using them are described. The main consumer preferences for pasty concentrates have been formed. A commodity assessment of meat zrazy using paste-like concentrates from lupine and amaranth seeds is given. The economic efficiency of food products using pasty concentrates has been calculated.
Keywords: Lupine paste concentrate, semi-finished meat products, commodity evaluation, microbiological evaluation.